Comparative pigment profiles of different Spirulina strains - Saleha, A. M.; Dhar, D. W.; Singh, P. K. (Research in Biotechnology, 2011)
Spirulina platensis (SP) has diverse biological activity. Due to the high content of highly valuable proteins, indispensable amino acids, ÃŽÂ²-carotene, vitamins, and other pigments, mineral substances,Ã‚Â indispensable fatty acids and polysaccharides, it has been found suitable for use as bioactive additive. In the current study seven strains ofÃ‚Â Spirulina were tested for its pigment profile. Phycobiliproteins are important accessory pigments in Spirulina. These consist of phycocyanin, (PC) allophycocyanin, (APC) and phycoerythrin, (PE). Highest PC and APC were recorded in Spirulina platensis (Sp7, mutant) followed by PC and APC contents recorded in its wild strain (Sp4). PC content in S. lonar (Sp6) and APC in Sp5 and Sp6 recorded third ranking. Among the strains tested Sp 4 showed significantly highest amount of pigments when compared to others. Interaction studies indicated that Sp7 showed highest PC content followed by its wild strain Sp4. The PC content in Sp2, Sp3 and Sp6 assumed third ranking at 15th day of incubation. Interaction analysis based upon LSD ranking showed the highest content was observed by the contents exhibited by Sp4Ã‚Â followed by Sp2, Sp3, Sp7, which was further followed by Sp5 at similar incubation time i.e. 25th day of incubation. In ÃŽÂ²-carotene analysis Strains x days of incubation interaction studies were significant and the top ranked combinations were Sp4 at 15th day (295.6ÃŽÂ¼g g-1 dryÃ‚Â weight), 20th day (289.5ÃŽÂ¼g g-1 dry weight) and at 25th day of incubation (282.4ÃŽÂ¼g g-1 dry weight).